Afterword: Cultivating Futures with Radical Hope - Thomas Stodulka (Humaniora, 2025)
Throughout Indonesia, educational experiments have become a prominent part of social life. From community learning spaces and feminist leadership schools to Islamic boarding schools adapted for digital economies, and from international nature schools to homeschooling networks of globally mobile families, various groups are rethinking not only what education could teach but also what kinds of futures it might cultivate. In these spaces, participants do more than transmit knowledge – they nurture relationships, skills, and moral sensibilities, planting seeds of radical hope that imagine lives and worlds that do not yet exist. Education thus becomes a practice of both experimentation and care, where the futures we hope for are cultivated patiently, attentively, and collaboratively.